Analysis of Inheritance Restrictions in Islamic Law: Slander in the Perspective of Qiyas Musawi and Legal Istinbath - Makka, Misbahul Munir; Saleh, Muhammad; Mamonto, Feraningsih; Yusuf, Nasruddin; Bilalu, Naskur (ANTMIND YOUTH EMPOWER FOUNDATION, 2024)
This study discusses slander in the context of inheritance according to Islamic law, especially in the context of inheritance restrictions from the perspective of Qiyas Musawi and Istinbath. The focus is on the issue of interfaith inheritance that is increasingly important in contemporary Islamic legal thought. The debate over the division of inheritance between non-Muslim heirs and the principles of traditional Islamic law is in the spotlight. This research uses an in-depth literature analysis method of relevant Islamic Legal sources to understand the views and solutions proposed by him. The results highlight the complexity and tension between traditional views of scholars and challenging contemporary perspectives, particularly in the context of Indonesia's religiously diverse society. This study provides a deep understanding of the issue of interfaith inheritance in Islamic law, investigating the perspectives of Qiyas Musawi and Istinbath, as well as their implications in the context of inheritance law in Indonesia.